What contributes to good patient outcomes in the home treatment of the severely mentally ill: study protocol of a multi-centre analysis - Stegbauer, Constance; Götz, Katja; Bauer, Erik; Bestmann, Beate; Ruprecht, Thomas; Szecsenyi, Joachim; Bramesfeld, Anke (BMC psychiatry, 2013)
While evidence is available that home treatment could be effective for treating severe mental illness, there is a lack of evidence on what exactly makes home treatment effective. The study presented here aims to develop recommendations for structures and processes in home treatment that are necessary for its effectiveness.
Published: 05 November 2013
Gesehen am 15.02.2022